Efficacy of pasireotide LAR for acromegaly: a prolonged real-world monocentric study - Favero, Vittoria; Zampetti, Benedetta; Carioni, Emanuela I.; Dalino Ciaramella, Paolo; Grossrubatscher, Erika; Dallabonzana, Daniela; Chiodini, Iacopo; Cozzi, Renato (Frontiers in Endocrinology, 2024)
Background: Acromegaly is caused by excessive growth hormone (GH) and insulin-like growth factor 1 (IGF1). Medical therapy plays a role as a treatment option for persistent disease after non-curative surgery or as a first-line therapy when surgery is not feasible. Pasireotide-LAR (Pas-LAR) is recommended for patients with acromegaly as second-line treatment.Aim: to evaluate the patients characteristics predictive of an adequate response to Pas-LAR and the long-term efficacy and safety of the Pas-LAR treatment.Methods: Data from 19 patients with active acromegaly, who were and resistant or intolerant to firstline medical therapy and were switched to pas-LAR have been retrospectively collected. We compared the baseline clinical and biochemical characteristics of patients who were found to respond to Pas-LAR therapy (responders, n=14) with those of patients who did not respond (non-responders, n=5). We then evaluated the Pas-LAR efficacy and safety during long-term follow-up in responders.Results: IGF1 normalization occurred in 71.4% of responders after one injection. IGF1 levels, [median(interquartile range) of the upper limit of the normal range (ULN) fold increase] were higher in non-responders compared to responders within the initial month of therapy [1.40(1.30-2.34) vs 0.70(0.55-1.25), respectively, p=0.009] and after three [1.77(1.74-2.29) vs 0.94(0.82-1.13), respectively, p=0.029] and six months [1.68(1.33-1.72) vs 1.00(0.65 -1.28), respectively, p=0.002].Out of 6 patients with symptomatic headache (all in responder group), 5 and 1 reported the resolution and improvement of headache, respectively, already after the first injection. Median HbA1c levels tended to increase from baseline to 6 months both in responder (36 mMol/Mol to 42 mMol/Mol) and non-responder patients (45 mMol/Mol to 48 mMol/Mol). During long term follow up, in the responder group 2 new patients developed diabetes. Tumor shrinkage was observed in 6 out of 7 evaluated responders, with no cases of size increase during the long-term follow-up.Pas-LAR is effective and safe and the early identification of responders is possible just after the first administration.